Prevalence and sociodemographic determinants of suboptimal glycemic control in persons with diabetes in Ghana: A systematic review and meta-analysis - Emmanuel Ekpor; Dorothy Wilson; Eric Peprah Osei; Bernard Abeiku Mensah; Samuel Akyirem (PLoS ONE, 2025)
Effective glycemic control is a cornerstone of diabetes management, essential for reducing the risk of complications and mortality. However, in Ghana, persistent limitations in diabetes management capacity present significant challenges to meeting recommended glycemic targets. This systematic review synthesizes the available evidence on the prevalence and sociodemographic determinants of suboptimal glycemic control among individuals with diabetes in Ghana. Relevant observational studies were obtained through a systematic search conducted on PubMed, Medline, Embase, Global health, Scopus, and Web of Science, from their inception to November 29, 2024. A random-effects meta-analysis was used to estimate the pooled prevalence of suboptimal glycemic control, accounting for heterogeneity across studies. Subgroup analyses were performed to explore potential sources of variability. We assessed publication bias statistically using Egger’s regression and Begg’s rank correlation test. Out of 1390 articles screened, 28 meet the inclusion criteria, comprising a total of 11,242 participants. The pooled prevalence of suboptimal glycemic control was 67.6% (95% CI: 64.2–70.8). When stratified by glycemic control measures, the prevalence was 69.2% (95% CI: 62.5–75.2) for fasting blood glucose levels ≥7.0 mmol/L and 66.9% (95% CI: 62.5–70.9) for hemoglobin A1c levels ≥7.0%. Sociodemographic factors such as age, income, gender, and ethnicity were found to be associated with suboptimal glycemic control. These findings underscore the substantial burden of suboptimal glycemic control among individuals with diabetes in Ghana, with over two-thirds not meeting recommended targets. There is an urgent need for targeted, context-specific interventions to address both clinical and systemic barriers to effective diabetes management in Ghana.